2020
DOI: 10.3390/app10082854
|View full text |Cite
|
Sign up to set email alerts
|

A System-Level Failure Propagation Detectability Using ANFIS for an Aircraft Electrical Power System

Abstract: The Electrical Power System (EPS) in an aircraft is designed to interact extensively with other systems. With a growing trend towards more electric aircraft, the complexity of interactions between the EPS and other systems has grown. This has resulted in an increased necessity of implementing health monitoring methods like diagnosis and prognosis of the EPS at the systems level. This paper focuses on developing a diagnostic algorithm for the EPS to detect and isolate faults and their root causes that occur at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In this work, three aircraft systems shown in the schematic diagram of FAVER (right side of fig 3) are examined: the engine, the ECS, and the fuel system. Previously, a simulation model of the EPS (Electrical Power System) was developed, with an Adaptive Neuro-Fuzzy Inference System (ANFIS) being implemented for its diagnosis [17]. It fits into the current framework but will not be replicated here.…”
Section: A Contributions In This Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, three aircraft systems shown in the schematic diagram of FAVER (right side of fig 3) are examined: the engine, the ECS, and the fuel system. Previously, a simulation model of the EPS (Electrical Power System) was developed, with an Adaptive Neuro-Fuzzy Inference System (ANFIS) being implemented for its diagnosis [17]. It fits into the current framework but will not be replicated here.…”
Section: A Contributions In This Papermentioning
confidence: 99%
“…The hot air then expands across the turbine blades (stations 4-5) and then passes through the core nozzle (stations 7-9). The cold bypassed air passes through a similar nozzle (stations [17][18][19] and mixes with the core flow to produce the thrust that moves the aircraft forward [18]. Bleed air is extracted from the compressor (station 3) based on demand, and supplied to the ECS and for anti-icing and deicing.…”
Section: A the Enginementioning
confidence: 99%
“…Taking the research object as an example, in the study of fault diagnosis of other complex nonlinear systems such as aircraft hydraulic systems, Jianhua Zhao [12] et al created the drop shock friction equation for the failure mode of single-degree-of-freedom bearing systems, providing a theoretical basis for fault prevention and diagnosis of Magnetic-liquid double suspension bearings (MLDSB). Cordelia Mattuvarkuzhali Ezhilarasu [13] et al created an electrical power system (EPS) diagnostic algorithm to detect and isolate line replaceable units (LRU) problems and their primary causes. Kenan Shen [14] et al suggested a new one-dimensional multichannel convolutional neural network (1DMCCNN) for diagnosing failure scenarios to improve aviation hydraulic system reliability and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Group D comprises model agnostic techniques suitable for aggregated analysis such as deep neural networks (DNN) [ 24 ], support vector machines (SVM) [ 25 ], hidden Markov models [ 26 ], and k-nearest neighbour classification [ 27 ]. Lastly, Group F include hybrid techniques that combine several model-based and/or data-driven approaches to compensate for the drawbacks in individual approaches, such as adaptive neuro-fuzzy inference systems (ANFIS) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%